2006
DOI: 10.1007/bf02708289
|View full text |Cite
|
Sign up to set email alerts
|

Temperature effects on surface activity and application in oxidation of toluene derivatives of CTAB-SDS with KMnO4

Abstract: The γ cmc values of CTAB-SDS decrease from 63⋅67 mN/m at 10°C to 36⋅38 mN/m at 90°C, slightly lower than those of either CTAB or SDS. Correspondingly, the CMC of CTAB-SDS decreases almost by half. The increase of surface activity of CTAB-SDS can be attributed to the relatively weak electrostatic interaction at high temperature, which is supported by the increase of solubility of CTAB-SDS with rise in temperature. Catalytic effect on oxidation of toluene derivatives with potassium permanganate follows the order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 19 publications
4
9
0
Order By: Relevance
“…The cmc of the SDS at 60°C was determined as 7.7 mM·l −1 , which is within the range of values reported in the literature for SDS in different solvents and temperatures [16–18].…”
Section: Resultssupporting
confidence: 80%
“…The cmc of the SDS at 60°C was determined as 7.7 mM·l −1 , which is within the range of values reported in the literature for SDS in different solvents and temperatures [16–18].…”
Section: Resultssupporting
confidence: 80%
“…Biosurfactants caused disturbance in balance of adhesive and cohesive forces resulting in sliding down of liquid droplet (Lv et al 2010;Biria et al 2013). It is pertinent to note that surface activities and CMC values of synthetic surfactants SDS and CTAB, calculated in this study also matched those reported in literature (Abood and Ajam 1985;Tang et al 2006). Anti-adhesiveness of the biosurfactant is important for its antiviral and biofilm removing abilities (Janek et al 2012;Gudina et al 2013).…”
Section: Discussionsupporting
confidence: 79%
“…4). As reported by Tang et al, the critical micelle concentration (CMC) for pure CTAB goes from 1.14 mM at 10°C to 1.07 mM at 90°C [20]. These values are almost two orders of magnitude lower than the CTAB concentrations used in this work.…”
Section: Morphology Vs Temperaturementioning
confidence: 55%